2017
DOI: 10.1039/c7sc00034k
|View full text |Cite
|
Sign up to set email alerts
|

Reduction chemistry of neptunium cyclopentadienide complexes: from structure to understanding

Abstract: Structural investigation on neptunium cyclopentadienyl organometallic complexes in the formal oxidation states II, III, and IV: similarities and differences between Np and U.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 72 publications
(74 reference statements)
6
78
0
1
Order By: Relevance
“…3 The S4 symmetry with four identical Cp rings around the Np IV centre assigned from combined IR 3 and FIR(far infra-red) 82 spectroscopic and powder X-Ray diffraction 83 data for the reddish brown crystals, and supported by a computational study, 8 has now been confirmed by single-crystal X-ray diffraction. 41 The computed 87 and was confirmed by subsequent investigations that found a non-zero electrical dipole moment in solution. 82 Further fitting of the low temperature magnetic susceptibility data 88,89 and also the optical spectra for the uranium analogue also suggested both D2h distortion, 87 whereas the single crystal X-ray diffraction analysis of UCp4 and photoelectron spectroscopy (using U(Cp Me )4 as a surrogate, Cp Me = C5H4Me) 90 indicated S4 symmetry for both.…”
Section: Cyclopentadienyl and Substituted Cyclopentadienyl Ligands Npsupporting
confidence: 56%
See 1 more Smart Citation
“…3 The S4 symmetry with four identical Cp rings around the Np IV centre assigned from combined IR 3 and FIR(far infra-red) 82 spectroscopic and powder X-Ray diffraction 83 data for the reddish brown crystals, and supported by a computational study, 8 has now been confirmed by single-crystal X-ray diffraction. 41 The computed 87 and was confirmed by subsequent investigations that found a non-zero electrical dipole moment in solution. 82 Further fitting of the low temperature magnetic susceptibility data 88,89 and also the optical spectra for the uranium analogue also suggested both D2h distortion, 87 whereas the single crystal X-ray diffraction analysis of UCp4 and photoelectron spectroscopy (using U(Cp Me )4 as a surrogate, Cp Me = C5H4Me) 90 indicated S4 symmetry for both.…”
Section: Cyclopentadienyl and Substituted Cyclopentadienyl Ligands Npsupporting
confidence: 56%
“…39,40 This nothwithstanding, the in situ reaction of suspended NpCl4 with sodium amalgam in diethyl ether produces a reactive, high-surface area form of NpCl3, that warrants further characterisation, or solvation studies as it has already proved its efficacy for metathesis reactions. 41 Unlike the many synthetically useful solvated uranium(III) halides, for neptunium, only [NpI3(THF)4] 42 has been reported, and its synthesis is from the metal which is generally not available to radiological facilities. Notably, in contrast to the synthesis of the isostructural UI3(THF)4 the Np does not require activation prior to the reaction with I2, and forms the thermally-stable product in very good yield.…”
Section: Neptunium Halide Starting Materialsmentioning
confidence: 99%
“…Both compounds, UCp 3 and PuCp 3 , form crystals that are isomorphic to the NpCp 3 analogue 4. For Cm and Bk, the cell parameters have been identified by Debye–Scherrer analyses together with a series of LnCp 3 complexes1e,1f all containing one axis doubled.…”
mentioning
confidence: 99%
“…A coordination environment of four Cp rings three establishing η 5 ‐ and one η 1 ‐coordination is also established in K[NpCp 4 ] the KCp adduct to NpCp 3 4. A symmetrical bonding of the η 5 ‐ coordinated Cp rings is produced (mean Np‐Ct Cp 251 pm, see footnote Table 1) together with a closer interaction to the η 1 ‐ coordinated C‐atom of the fourth Cp ring (Np−C 275.2(7) pm) showing that Cp in KCp is a better Lewis base than in NpCp 3 .…”
mentioning
confidence: 99%
“…Unfortunately, the drawback associated with the presence of a nuclear spin cannot be overcome by simply choosing another neptunium isotope, since 237 Np is the only one with half-life long enough to be practically useful. For this reason, even if several high-symmetry, potentially interesting Np IV -based monometallic clusters have been synthesized and reported in the literature [34,35], the unavoidable presence of hyperfine interaction is expected to strongly limit their performances as SMM. The effect on the non-Kramers Np III ion could be even worse.…”
Section: Monometallic Complexesmentioning
confidence: 99%